Thermal properties of passion fruit juice as affected by temperature and water content - Gratão, Ana Carolina Amaral; Silveira Jr., Vivaldo; Polizelli, Marcos Alexandre [UNESP]; Telis-Romero, Javier [UNESP] (Wiley, 2004)
The specific heat, thermal conductivity and density of passion fruit juice were experimentally determined from 0.506 to 0.902 (wet basis) water content and temperatures from 0.4 to 68.8C. The experimental results were compared with existing and widely used models for the thermal properties. In addition, based on empiric equations from literature, new simple models were parameterized with a subset of the total experimental data. The specific heat and thermal conductivity showed linear dependency on water content and temperature, while the density was nonlinearly related to water content. The generalized predictive models were considerably good for this product but the empiric, product-specific models developed in the present work yield better predictions. Even though the existing models showed a moderate accuracy, the new simple ones would be preferred, because they constitute an easier and direct way of evaluating the thermal properties of passion fruit juice, requiring no information about the chemical composition of the product, and a reduced time of the estimation procedure, as the new empiric models are described in terms of only two physical parameters, the water content and the temperature. © Copyright 2005, Blackwell Publishing All Rights Reserved.
Keywords: Composition; Consumer products; Heat resistance; Heat treatment; Mathematical models; Proteins; Specific heat; Thermal conductivity; Water; Empiric equation; Product-specific model; Thermal properties; Water contents; Fruit juices; Passiflora edulis